An electromyographical analysis of purposive muscle activity and appearance of muscle silent period in archery shooting - Nishizono, H.; Nakagawa, K.; Suda, T.; Saito, K. (Japanese Journal of Physical Fitness and Sports Medicine, 1984)
Shooting an arrow is a typical example of the physiological neck reflex. To get a good record in the archery competition, highly reproducible release is required during the drawing of a bow.In this study, first, the mechanics of shooting were analysed by means of EMG, progressive photographing and bow strain signals, employing two groups of college student archers (semi-skilled and unskilled) . These results were compared with those of the world top-class archers. And second, the rate of muscle silent period appearance, its latent time and release reaction time were measured from the three groups of college student archers (skilled, semi-skilled and unskilled) . The following results were obtained:1. Some distinct differences were recognized in muscle activities during shooting, such as "set up", "draw", "full draw", "release" and "follow through" between the top-class archers and college archers (semi-skilled and unskilled) .2. In the case of two top-class archers, muscle silent period prior to release was observed in m. deltoideus (pars acrominalis) of both arms and m. trapezius (pars transversa) of the pushing arm.3. In the skilled college student archers, high rate of silent period appearance (70-100%) were observed and the values of its latent time and release reaction time falled in a very narrow range of 110-120 msec and 170-180 msec, respectively.4. Before the release, when m. deltoideus of the pulling arm was silent, ipsilateral m. trapezius began action. This muscle activity was cleary observed almost only in the case of skilled archers. Hence, this pattern of muscle activity may be accomplished by long time training.